Pengaruh Perilaku Konsumen Terhadap Keputusan Pembelian Kue Khas Ternate (Bagea, Makron dan Roti Kenari) - Alhadar, Lidia Ferial; Sirat, Abdul Hadi (Jurnal Manajemen Sinergi, 2022)
The purpose of this study is to know and analyze: (1)The influence of cultural factors on buying decisions typical ofTernate; (2) The influence of social factors on the purchase decisionof the typical cake of Ternate; (3) The influence of personal factorson buying decisions typical of Ternate; (4) Influence ofpsychological factor to decision of purchasing cake typical ofTernate; and (5) The influence of cultural, social, personal andpsychological factors on the buying decision of Ternate cakessimultaneously.Methodology: The test equipment used is multiple regressionanalysis using statistical package for social scientists (SPSS) as astatistical test tool. The number of samples of the study were 100consumers.Finding: H1, H2, H3, H5, and H5 are accepted at the 5%confidence level.Conclusion: The results showed that: (1) Cultural factors (X1) havea positive and significant effect partially on the purchase decision oftypical cakes ternate. These results are based on t arithmetic valuesgreater than t table values and smaller significance values thanalpha; (2) Social factors (X2) have a positive and partially significanteffect on buying decision of typical cakes of ternate. This result isbased on a larger F count value and a smaller significance valuethan the alpha value; (3) Personal factors (X3) have a positive andpartially significant effect on buying decision of Ternate typical cake.This result is based on a larger F count value and a smallersignificance value than the alpha value; (4) psychological c factors(X4) have a positive and partially significant effect on buyingdecision of Ternate typical cake. This result is based on a larger Fcount value and a smaller significance value than the alpha value;and (5) Cultural factors, social factors, personality factors, andpsychological factors have a positive and significant influencesimultaneously on the decision to purchase a typical cake Ternate.